Clinical efficacy of SARS-CoV-2 Omicron-neutralizing antibodies in immunoglobulin preparations for the treatment of agammaglobulinemia in patients with primary antibody deficiency. - Karbiener, Michael; Kindle, Gerhard; Meyts, Isabelle; Seppänen, Mikko R.J.; Candotti, Fabio; Kamieniak, Marta; Ilk, Reinhard; Kreil, Thomas R.; Seidel, Markus G.; Abd Elaziz, Dalia; Abdelkader Sohilla, Lofty M.; Abitbol, Avigaelle; et al. (Journal of Medical Virology, 2024)
Immunocompromised individuals are at significantly elevated risk for severe courses of coronavirus disease 2019 (COVID-19). In addition to vaccination, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) neutralizing antibodies (nAbs) have been applied throughout the pandemic, with time of treatment onset and potency against the currently prevailing virus variant identified as relevant factors for medical benefit. Using data from the European Society for Immunodeficiencies (ESID) registry, the present study evaluated COVID-19 cases in three groups of patients with inborn errors of immunity (IEI; 981 agammaglobulinemia patients on immunoglobulin replacement therapy (IGRT); 8960 non-agammaglobulinemia patients on IGRT; 14 428 patients without IGRT), and the neutralizing capacity of 1100 immunoglobulin lots against SARS-CoV-2 ("Wuhan" and Omicron strains), throughout 3 years. From the first (2020/2021) to the second (2021/2022) cold season, i.e., during the virus drift to the more contagious Omicron variants, an increase in case numbers was recorded that was comparable ( 2- to 3-fold) for all three study groups. During the same period, immunoglobulin lots showed a profound nAb increase against the archetypal SARS-CoV-2 strain, yet only low levels of Omicron nAbs. Notably, shortly before the third (2022/2023) cold season, Omicron-neutralizing capacity of released immunoglobulin lots had plateaued at high levels. From the second to the third cold season, COVID-19 cases dropped markedly. While a 6-fold case reduction was recorded for the groups of non-agammaglobulinemia patients on IGRT and IEI patients not receiving IGRT, the decline was 30-fold for the group of agammaglobulinemia patients on IGRT. These findings suggest a substantial COVID-19-protective effect of IGRT, at least for distinct groups of antibody-deficient patients.
EVALuna2:581110